(untitled) (Journal of Atomic and Molecular Sciences, 2014)
Electronic states of the m-C_6H_4F^+_2 ion were studied by using the CASPT2 and CASSCF methods in conjunction with a contracted atomic natural orbital (ANOL) basis set. For the five lowest-lying states, geometries and adiabatic excitation energies (T_0) were calculated at the CASPT2 level. The CASPT2 T_0 values and CASPT2 T'_v values are in reasonable agreement with the available experimental data. The assignments of the B, C, and D states of the m-C_6H_4F^+_2 ion were difficult since the three states are closely lying. Based on the CASPT2 T_0 calculations, the X, A, B, C, and D states of the m-C_6H_4F^+_2 ion were assigned to 1^2A_2, 1^2B_1, 2^2B_1, 1^2A_1, and 1^2B_2, respectively, which supports the suggested assignment of the lowest excited state to ^2B_1 by Tsuchiya et al. based on their experiments.